Investigator's Global Assessment of Chronic Prurigo: A New Instrument for Use in Clinical Trials - Claudia Zeidler; Manuel P. Pereira; Matthias Augustin; Mary Spellman; Sonja Ständer (Medical Journals Sweden, 2021)
Chronic prurigo is a pruritic disease characterized by the development of pruriginous lesions due to scratching. The number of lesions is representative of the stage of the disease, while the presence of excoriations reflects the scratching activity. Aim of this study was to validate a new developed tool for the objective assessment of chronic prurigo. Investigator's Global Assessment scales for stage and activity were completed for 187 patients with chronic prurigo, who also reported patient-reported outcomes for itch intensity and quality of life. To assess the reliability and objectivity of the Investigator's Global Assessment, 5 independent raters completed the Investigator's Global Assessment scales for 8 patients twice. The scores increased with increased intensity of pruritus. The Investigator's Global Assessment stage scales correlated strongly with each other (Kendall's-tau-b 0.62) and moderately with the Investigator's Global Assessment activity scale (Kendall's-tau-b 0.47). Intra-rater test-retest reliability was excellent for all items, while the congruence among raters was very good for Investigator's Global Assessment - chronic prurigo activity (Kendall's W 0.84) and good for Investigator's Global Assessment stage scales (Kendall's W 0.747). Investigator's Global Assessment - chronic prurigo stage and activity are thus the best Investigator's Global Assessment instruments for use in assessing chronic prurigo.